Atmospheric nitrate formation pathways in urban and rural atmosphere of Northeast China: Implications for complicated anthropogenic effects. (1st March 2022) - Li, Zhengjie; Walters, Wendell W.; Hastings, Meredith G.; Song, Linlin; Huang, Shaonan; Zhu, Feifei; Liu, Dongwei; Shi, Guitao; Li, Yilan; Fang, Yunting
Abstract: Effects of human activities on atmospheric nitrate (NO3 - ) formation remain unclear, though the knowledge is critical for improving atmospheric chemistry models and nitrogen deposition reduction strategies. A potentially useful way to explore this is to compare NO3 - oxidation processes in urban and rural atmospheres based upon the oxygen stable isotope composition of NO3 - (Δ 17 O–NO3 - ). Here we compared the Δ 17 O–NO3 - from three-years of daily-based bulk deposition in urban (Shenyang) and forested rural sites (Qingyuan) in northeast China and quantified the relative contributions of different formation pathways based on the SIAR model. Our results showed that the Δ 17 O in Qiangyuan (26.2 ± 3.3‰) is significantly higher ( p < 0.001) than in Shenyang (24.0 ± 4.0‰), and significantly higher in winter (Shenyang: 26.1 ± 6.7‰, Qingyuan: 29.6 ± 2.5‰) than in summer (Shenyang: 22.7 ± 2.9‰, Qingyuan: 23.8 ± 2.4‰) in both sites. The lower values in the urban site are linked with conditions that favored a higher relative contribution of nitrogen dioxide reaction with OH pathway (0.76-0.91) than in rural site (0.47-0.62), which should be induced by different levels of human activities in the two sites. The seasonal variations of Δ 17 O–NO3 - in both sites are explained by a higher relative contribution of ozone-mediated oxidation chemistry and unfavorable conditions for the OH pathway during winter relative to summer, which is affected by human activities and seasonal meteorological condition change. Based on Δ 17 O, wintertime conditions led to a contribution of O3 related pathways (NO3 + DMS/HC and N2 O5 hydrolysis) of 0.63 in Qingyuan and 0.42 in Shenyang, while summertime conditions led to 0.15 in Qingyuan and 0.05 in Shenyang. Our comparative study on Δ 17 O–NO3 - between urban and rural sites reveals different anthropogenic effects on nitrate formation processes on spatial and temporal scales, illustrating different responses of reactive nitrogen chemistry to changes in human activities. Graphical abstract: Image 1 Highlights: Δ 17 O of bulk deposited NO3 − was lower in urban versus rural atmosphere. Δ 17 O–NO3 - was lower in summer and higher in winter in both urban and rural sites. Urban nitrate yielded lower Δ 17 O than the rural site due to chemistry differences. Lower Δ 17 O values are due to higher contributions of the OH formation pathway.